Faktor risiko karies gigi pada anak : A Scoping Review - Sintha, Syahrilla; Ratna Laksmiastuti, Sri; Widhiyaningsih, Dhyani (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: The most common dental and oral health problem in children is dental caries. This is because children are individuals who are not yet independent and still need a parent figure to maintain their dental and oral health. One of the comprehensive caries management is caries risk assessment. The importance of analyzing caries risk factors. The risk of caries in each individual varies depending on many things, including environmental and socio-economic conditions. Objective: To analyze the risk factors for dental caries in children so that efforts can be planned to prevent dental caries in children. Method: Descriptive observational research through a scoping review with a literature search method based on Population, Concept, and Context (PCC) criteria and in accordance with PRISMA guidelines on the Google Scholar and PubMed databases. Results: There were 15 articles that met the eligibility criteria and were included in this study. Analysis of journal articles shows that each risk factor for dental caries in children is different. Conclusion: Risk factors are factors that contribute indirectly to dental caries. Risk factors for dental caries in children vary depending on many things, such as environmental and socio-economic conditions.